Whole body MRI of the non-human primate using a clinical 3T scanner: initial experiences - Li, Chun-Xia; Zhang, Xiaodong (Quantitative Imaging in Medicine and Surgery; Vol 7, No 2 (April 25, 2017): Quantitative Imaging in Medicine and Surgery (Medical Engineering and Magnetic Resonance Physics special issue), 2017)
With the advent of parallel imaging MRI techniques, whole-body MRI is being increasingly used in clinical diagnosis. However, its application in preclinical research using large animals remains very limited. In the present study, the whole-body MRI techniques for adult macaque monkeys were explored using a conventional clinic 3T scanner. The T1, T2 anatomical images, and MR angiography of adult macaque whole bodies were illustrated. The preliminary results suggest whole-body MRI can be a robust tool to examine multiple organs of non-human primate (NHP) models from head to toe non-invasively and simultaneously using a conventional clinical setting. As NHPs are intensely used in biomedical research such as HIV/AIDS and vaccine discovery, whole body MRI techniques can have a wide range of applications in translational research using NHPs.